Data Mining Analysis Using Bayes Method to Measure Damage Rate of Motor Engines: Analisa Data Mining Menggunakan Metode Bayes Untuk Mengukur Tingkat Kerusakan Mesin Motor - Sheryl Febry irianti Simanjuntak; Erlin Elisa (International Journal of Technology Vocational Education and Training, 2020)
Workshop is a business that is engaged in the automotive business such as a medium-sized business down the workshop providing complete motorcycle spare parts, not only that the workshop in general also serves motorcycle service and accepts light and heavy service for all types of motorcycle brands. Hendri Motor is one of the workshops in Piayu which already has many customers who receive motorcycle service every month in Batam City. The level of motor damage that can be categorized as motor damage is mild damage, moderate damage, or severe damage because most users prefer to change oil once a month, in fact there are also those who have passed the specified time period to replace oil, for example it can be up to 2 months to 5 the month does not replace new oil. Analysis is needed to see the pattern of consumer data so that it can produce motor service probabilities that will later be useful for categorizing in light or heavy service. From so much consumer data, Data Mining is performed using the Naïve Bayes. The results of this mining activity are expected to provide a decision to see the prediction patterns of motor service consumer behavior